Congenital midline nasal mass: cases series and review of the literature - Wang, I-Jen; Lin, Shoei-Loong; Tsou, Kuo-Inn; Hsu, Ming-Che; Chiu, Wen-Ta; Tsai, Shin-Han; Lee, Liang-Ming; Lin, Tien-Jen (The Turkish Journal of Pediatrics, 2010)
Encephalocele, glioma and dermoid cyst are the most common midline nasal masses. Given their potential for intracranial extension, prompt treatment is necessary to prevent complications. Herein, we present two cases of midline nasal masses. A comparison was made to delineate the differences between their clinical courses, treatments and outcomes. Case 1 was a baby girl with respiratory distress beginning at birth. Nasal glioma without definite intracranial extension was present. The mass was completely excised with the aid of a video-assisted endoscope without complications. At follow-up two years after surgery, no recurrence was noted. Case 2 was a two-year-old boy with a midline nasal dermoid cyst. Extirpation of the lesion through a vertical-dorsal approach was performed. He was discharged three days after surgery with a satisfactory aesthetic result.